Three-Dimensional Surface Reconstruction of the Human Cochlear Nucleus: Implications for Auditory Brain Stem Implant Design - Tarabichi, Osama; Kanumuri, Vivek V.; Klug, Julian; Vachicouras, Nicolas; Duarte, Maria J.; Epprecht, Lorenz; Kozin, Elliott D.; Reinshagen, Katherine; Lacour, Stéphanie P.; Brown, M Christian; Lee, Daniel J. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The auditory brain stem implant (ABI) is a neuroprosthesis placed on the surface of the cochlear nucleus (CN) to provide hearing sensations in children and adults who are not candidates for cochlear implantation. Contemporary ABI arrays are stiff and do not conform to the curved brain stem surface. Recent advancements in microfabrication techniques have enabled the development of flexible surface arrays, but these have only been applied in animal models. Herein, we measure the surface curvature of the human CN and adjoining regions to assist in the design and placement of next-generation conformable clinical ABI arrays. Three-dimensional (3D) reconstructions from ultrahigh T1-weighted brain magnetic resonance imaging (MRI) sequences and histologic reconstructions based on postmortem adult human brain stem specimens were used.Design This is a retrospective review of radiologic data and postmortem histologic axial sections.Setting This is set at the tertiary referral center.Participants Data were acquired from healthy adults.Main Outcome Measures The main outcome measures are principal curvature values (Kmin and Kmax) and global radius of curvature.Results The CN was successfully extracted and rendered as a 3D surface in all cases. Significant curvatures of the CN in both histologic and radiographic reconstructions were found with global radius of curvature ranging from 2.08 to 8.5 mm. In addition, local curvature analysis revealed that the surface is highly complex.Conclusion Detailed rendering of the human CN is feasible using histology and 3D MRI reconstruction and highlights complex surface topography that is not recapitulated by contemporary stiff ABI arrays.
Keywords: auditory brain stem implant; cochlear nucleus; curvature; surface curvature